Pharmacology of Cyclic Peptides: Vancomycin and Oxytocin as Paradigms - Schulze, Johannes (Protein and Peptide Letters, 2014)
Cyclic oligopeptides have been introduced into pharmacological use for uses as diverse as selective release of the clotting factor VIII (von Willebrandt factor) by vasopressin, immune modulation by cyclosporin and antibacterial activity by vancomycin. Even now, 60 years after the first isolation of vancomycin (3,4) and the sequencing of oxytocin (48) these compounds have not lost their important role in clinical use. With regard to pharmacological properties oxytocin (as the peptide identic to the human sequence) and vancomycin (as a nonribosomal bacterial peptide) epitomize the swath of cyclic peptide properties.
Keywords: vancomycin